Mediasi Kepuasan Nasabah Pada Pengaruh Kualitas Pelayanan dan Citra Perusahaan Terhadap Loyalitas (Studi Pada PT. Bank Syariah Mandiri KCP Pandeglang) - Agustiansyah, Eka Cahya; Taufik, Edi Rahmat (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2019)
Generally unsatisfied customers will convey bad experiences to others and it will cause big losses for the company. This study aims to improve customer loyalty through service quality and corporate image mediated by customer satisfaction. The research used SEM-PLS method which was done on 100 BSM customers in KCP Pandeglang using accidental sampling technique. The result of the research shows that service quality has positive and significant influence to customer loyalty, corporate image has no effect to customer loyalty, service quality has positive and significant effect to customer satisfaction, corporate image has positive and significant impact to customer satisfaction, and satisfaction has positive and significant impact to customer loyalty. Customer satisfaction is proven to mediate partial service quality to customer loyalty